Register of a New Nidification Substrate for Melipona subnitida Ducke (Hymenoptera, Apidae, Meliponini); Termitaria of the Arboreal Nesting Termite Constrictotermes cyphergaster Silvestri (Isoptera, Termitidae, Nasutitermitinae) - Carvalho, Airton Torres; Koedam, Dirk; Imperatriz-Fonseca, Vera Lucia (Sociobiology, 2014)
ABSTRACT - Melipona subnitida, popularly also known as jandaíra, is the most frequently domesticated bee in the dry northeastern part of Brazil, and like most other stingless bee species nest in hollow spaces in trees. However, in a small region of Chapada do Araripe plateau the nest of this bee can also be regularly found within living arboreal termite nests of Constrictotermes cyphergaster. Here we describe the structure and content of such a bee nest when we transferred it from a formerly collected termite nest into a wooden nest box, and present complementary information based on an untouched, feral nest. We hypothesize whether or not this nesting habit of M. subnitida is an adaptation to a deficiency in pre-existing cavities in trees locally.